The healthy indoor environment how to assess occupants' wellbeing in buildings - Bluyssen, Philomena M. (Routledge, 2014)
"The Healthy Indoor Environment aims to help architects, building engineers and anyone concerned with the wellbeing of building occupants to better understand the effects of spending time in buildings on health and comfort. In three clear parts dedicated to mechanisms, assessment and analysis, the book looks at different indoor stressors and their effects on wellbeing in a variety of scenarios with a range of tools and methods"-- Provided by publisher.